Learning Strategy: Exposure Visits - Mukhopadhyay, Dr Prama; Mitra, Avik; Iqbal, Md.; Biswas, Niloy (International Rice Research Institute, 2026)
As part of the CGIAR Gender and Social Inclusion (GSI) Accelerator under the EMPOWER initiative, two exposure visits were organised for women farmers participating in Learning Labs (LLs) in West Bengal, India. Operational for over two years in the climate-vulnerable districts of South and North 24 Parganas, these Learning Labs are sites of piloting the gender responsive Socio-Technical Innovation Bundles (STIBs) approach. The LLs aim to enable women farmers to access integrated bundles of technical, institutional, financial, and social interventions to strengthen resilience to climate change. The exposure visits were a deliberate component of these innovation bundles and were designed as an experiential, peer-based learning strategy. By engaging directly with women farmers involved in similar agri-based livelihood activities in other regions, participants observed how technical practices, institutional arrangements, access to finance, risk-mitigation mechanisms, and collective action interact in practice to generate sustainable livelihood outcomes. The visits contributed to enhanced confidence, expanded aspirations, and deeper practical understanding among participating women.